Interpretasi aksi teo-ecology dan transendentalisme terhadap pelestarian lingkungan - Alam, Lukis (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2020)
This research presents a reading of the aspects of religious transidentalism in presenting the narrative of environmental preservation. Certainly in that context, the author tries to illustrate with teo-ecology construction based on quranic insights. Therefore, man as a subject, occupies a wide space in realizing the idea of godliness and humanistics in managing the nature and environment that God has given. Result of this study provides a major argument against the meaning of the Quran as the basis of environmental Teo-Ecology which contributes the deepest contribution, so that environmental preservation is always encouraged. In addition, in environmental preservation is necessary also the construction of ecological ethics humanizes the environment itself, so that a balance arises there. Lastly, it is no less important to elicit an attitude of transcendentalism in man that as god's representative on Earth must have mentally managed the environment well.